PERFORMANCE IMPROVEMENT OF FEMTOSECOND PULSES SELECTION DEVICE FOR CHEMICAL PROCESSES REMOTE SPECTROMETRIC CONTROL - K. V. Melnikov; V. A. Melnikov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Results of switching velocity performance improvement for high voltage switches based on MOSFTEs are presented. Parameters of developed Q-switch driver for femtosecond laser pulse picker to use at remote spectrometric control laser radiation unit are given. Miller effect influence for high voltage MOSFET switching speed experimentally investigated.